EFEKTIFITAS SISTEM REWARD DAN PUNISHMENT TEHADAP PENINGKATAN KINERJA KARYAWAN - Siti Mardah; Dwi Wahyu Artiningsih; Nor Aina (KINDAI, 2023)
Abstract: Competition between companies is getting higher, making companies have to be able to maintain the continuity of the company by further improving the capabilities of its human resources. Through competent and good quality employees, companies can improve their performance through reward and punishment. This research was conducted at PT Barito Berlian Motor Banjarbaru with a total population of 173 people and 121 people who were sampled from the total population using the slovin formula. This type of research is quantitative which is descriptive and associative of causal relationships. This research used the IBM version of the SPSS 22 test tool which the results tested were validity and reliability tests, classical assumption tests, hypothesis tests, multiple linear regression tests and correlation tests. For both variables X1 and X2 have a positive and significant influence simultaneously on employee performance. Correlationally, the relationship between reward and punishment variables has a positive and significant influence as well. Keywords: Reward, Punishment, Employee Performance